2021
DOI: 10.1186/s12967-021-03123-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis revealed that IL4I1 promoted ovarian cancer progression

Abstract: Background Ovarian cancer was one of the leading causes of female deaths. Patients with OC were essentially incurable and portends a poor prognosis, presumably because of profound genetic heterogeneity limiting reproducible prognostic classifications. Methods We comprehensively analyzed an ovarian cancer single-cell RNA sequencing dataset, GSE118828, and identified nine major cell types. Relationship between the clusters was explored with CellPhone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…Prolif-TAMs were identified in a pan-cancer study [12] and in studies of several cancer types, including gastric cancer [42], CRC [12], fibrosarcoma [37], prostate cancer [66], NSCLC [27,61], OVC [67], and CNS tumors [34,52]. This population is characterized by the expression of proliferation marker Ki-67 (MKI67), and cell cycle genes, such as cyclin-dependent kinase 1 (CDK1) and cell division cycle 45 (CDC45).…”
Section: Trends In Immunologymentioning
confidence: 99%
See 1 more Smart Citation
“…Prolif-TAMs were identified in a pan-cancer study [12] and in studies of several cancer types, including gastric cancer [42], CRC [12], fibrosarcoma [37], prostate cancer [66], NSCLC [27,61], OVC [67], and CNS tumors [34,52]. This population is characterized by the expression of proliferation marker Ki-67 (MKI67), and cell cycle genes, such as cyclin-dependent kinase 1 (CDK1) and cell division cycle 45 (CDC45).…”
Section: Trends In Immunologymentioning
confidence: 99%
“…Notably, TAM clusters feature various metabolic patterns, as inferred from scRNA-seq data through pathway analysis. For example, studies on human NSCLC, PDAC, and OVC indicated that Angio-TAMs highly express hypoxia-related metabolic genes, such as HIFA and SLC2A1 [28,49,67]. In addition, IFN-TAMs were reported to express genes of tryptophan catabolism in a human pan-cancer study [12].…”
Section: Metabolic Diversity Of Tamsmentioning
confidence: 99%
“…So far, there have been no studies reporting an association between HTLV-1 and OC. However, HTLV-1 infection can promote T cell proliferation by tampering with several core signalling pathways of T cell function [57], and the relationship between T cell function and OC has been demonstrated in several studies [49,50,52]. From this, we speculate that HTLV- We developed a prognostic pro le of four lncRNAs associated with iron toxicity, and found it could effectively identify patients with high-risk OC.…”
Section: Discussionmentioning
confidence: 85%
“…found that HSP10 produced by ovarian tumour cells suppressed the expression of CD3-zeta, , a key component of T cell activation, in T cells [50], and OC patients with lower T cell CD3-zeta expression have been found to exhibit shorter survival times [51]. In addition, IL4I1 has been found to impair T-cell activation, block T cell proliferation and differentiation, and thus promote OC proliferation, migration, and invasion [52]. From this, we hypothesized that T cell activation may prolong OC patient survival, while T cell suppression may be closely associated with low survival in OC patients.…”
Section: Discussionmentioning
confidence: 99%
“…As technology advances, single-cell sequencing can be used to identify the expression patterns in individual cell clusters. A recent study attempted to apply scRNA-seq-based signatures in prognostic prediction in ovarian cancer ( 45 ). The scRNA-seq-based signatures revealed the roles of macrophages in ovarian cancer progression and showed robust performance in predicting patient prognosis.…”
Section: Discussionmentioning
confidence: 99%